Doxorubicin Loaded Thermosensitive Magneto-Liposomes Obtained by a Gel Hydration Technique: Characterization and In Vitro Magneto-Chemotherapeutic Effect Assessment - Stefan Nitica; Ionel Fizesan; Roxana Dudric; Felicia Loghin; Constantin Mihai Lucaciu; Cristian Iacovita (MDPI AG, 2022)
The combination of magnetic hyperthermia with chemotherapy is considered a promising strategy in cancer therapy due to the synergy between the high temperatures and the chemotherapeutic effects, which can be further developed for targeted and remote-controlled drug release. In this paper we report a simple, rapid, and reproducible method for the preparation of thermosensitive magnetoliposomes (TsMLs) loaded with doxorubicin (DOX), consisting of a lipidic gel formation from a previously obtained water-in-oil microemulsion with fine aqueous droplets containing magnetic nanoparticles (MNPs) dispersed in an organic solution of thermosensitive lipids (transition temperature of ~43 °C), followed by the gel hydration with an aqueous solution of DOX. The obtained thermosensitive magnetoliposomes (TsMLs) were around 300 nm in diameter and exhibited 40% DOX incorporation efficiency. The most suitable MNPs to incorporate into the liposomal aqueous lumen were Zn ferrites, with a very low coercive field at 300 K (7 kA/m) close to the superparamagnetic regime, exhibiting a maximum absorption rate (SAR) of 1130 W/gFe when dispersed in water and 635 W/gFe when confined inside TsMLs. No toxicity of Zn ferrite MNPs or of TsMLs was noticed against the A459 cancer cell line after 48 h incubation over the tested concentration range. The passive release of DOX from the TsMLs after 48h incubation induced a toxicity starting with a dosage level of 62.5 ug/cm2. Below this threshold, the subsequent exposure to an alternating magnetic field (20-30 kA/m, 355 kHz) for 30 min drastically reduced the viability of the A459 cells due to the release of incorporated DOX. Our results strongly suggest that TsMLs represent a viable strategy for anticancer therapies using the magnetic field-controlled release of DOX.